2019
DOI: 10.3166/phyto-2019-0179
|View full text |Cite
|
Sign up to set email alerts
|

High in vitro Antioxidant Capacities of AlgerianCleome arabicaLeaves’ Extracts

Abstract: The aim of this study was to evaluate the antioxidant capacities of Cleome arabica leaves’ extract collected on two seasons in the town of Laghouat steppe region of Algeria. Five common tests for measuring antioxidant capacities were used to compare with three standard antioxidants: measurement of free radical scavenging activity with 1,1-diphenyl-2-picrylhydrazyl radical (DPPH·) and 2,2ʹ- azinobis(3-ethylbenzo-thiazo-line-6-sulfonate) (ABTS·+) radical cation, measurement of total antioxidant capacities with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…This indicated that ZNE and F6 are enriched in polyphenolic metabolites and flavonoids, in agreement with previous reports (Kumar et al, 2002;Bodroth and Das, 2012;Sonia and Singh, 2019;Zandifar et al, 2020). This finding is relevant, especially that therapeutic and antioxidant properties of plant extracts are mostly attributed to flavonoids and polyphenols (Bhosale et al, 2020;Seglab et al, 2021;Slika et al, 2022). Natural polyphenols are plant secondary metabolites with two or more phenol rings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This indicated that ZNE and F6 are enriched in polyphenolic metabolites and flavonoids, in agreement with previous reports (Kumar et al, 2002;Bodroth and Das, 2012;Sonia and Singh, 2019;Zandifar et al, 2020). This finding is relevant, especially that therapeutic and antioxidant properties of plant extracts are mostly attributed to flavonoids and polyphenols (Bhosale et al, 2020;Seglab et al, 2021;Slika et al, 2022). Natural polyphenols are plant secondary metabolites with two or more phenol rings.…”
Section: Discussionsupporting
confidence: 91%
“…They are also anticancer agents that can inhibit cell cycle progression, induce apoptosis, inhibit metastasis (Bhosale et al, 2020). Flavonoids are natural polyphenols with documented anticancer and antioxidant properties (Seglab et al, 2021;Slika et al, 2022). As expected, the TFC and TPC values of ZNE were higher than those of F6, in agreement with the results of the HPLC-PDA-MS/MS, which revealed that F6 is partially purified and had less polyphenolic and flavonoid metabolites.…”
Section: Discussionsupporting
confidence: 82%
“…The plant is used in traditional medicine as a diuretic and against rheumatism; it is also a therapeutic and anti-bacterial plant (Ladhari et al 2013). The effect of this species has also been proven against different orders of insects (Doumandji-Mitiche and Doumandji 1993;Ozenda 1991;Aouinty et al 2006;Kemassi and Oueld El-hadj 2008;N'Guessan et al 2009;Lebouz 2010;Kemassi et al 2012;Koita et al 2012;Habbachi et al 2013;Merabti et al 2015;Benhissen 2016;Merabti 2016, Masna 2016Korichi-Almi et al 2016;Almi et al 2016;Benhissen et al 2018;Bekhakheche et al 2018;Seglab et al 2019;Boublata et al 2020;Saadane et al 2021;. For the present study, the plant was collected in the Bousaada region (M'sila, Algeria) (33°48′24″ N latitude, 2°52′56″ E longitude).…”
Section: Cleome Arabica (Capparidaceae)mentioning
confidence: 99%
“…It is widely growing in desert sandy habitats of Sinai, Egypt, and many parts of North Africa (Kamel et al, 2010). This herb possesses different biological activities, containing anti-inflammatory, anti-COVID-19, genotoxicity, antidiabetic, antioxidant, and antimicrobial effects (Takhi et al, 2011;Edziri et al, 2013;Zaki et al, 2020;Khlifi et al, 2021 andSeglab et al, 2021;).…”
Section: Introductionmentioning
confidence: 99%